Observations Results of Electron Density Profile by S-310JA-7 Rocket - Miyazaki, Shigeru; Ogawa, Tadahiko; Mori, Hirotaka; Yamagishi, Hisao (1981)
P(論文) In order to measure the ionospheric plasma in the polar region, a sounding rocket was fired at 221550LT on March 27,1978 from Syowa Station in Antarctica. Maximum electron density of about 1×(10)^6(cm)^<-3> was obtained, which is the highest value among the observational results obtained during 1971-1978. departmental bulletin paper